(3aJhM GdMHTI GdeSei HgLI GdReGfs - (3TgGH GdOjf CMeO Hf YHO GdbGOQ Hf SGde Hf YKeGf GdSGcf HMHjQGf GdeYQha HYQH abjg,J (B940 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdefGf Ph GdaVd hGdLhO hGdEMSGf s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B153s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B410 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B196 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdHdOjI HGdGScfOQjI (B(2294 (3H(B) s
Keywords: (3GdJGQjNs